A case study of one high performance baseball coach's experiences within a learning community. Issue 1 (1st January 2016) - Kuklick, Clayton R.; Gearity, Brian T.; Thompson, Melissa; Neelis, Laurie
Abstract : The purpose of the present study was to examine the learning experiences of a high performance, head baseball coach within a learning community. We drew upon the barriers and enablers of a learning community to structure the current study's learning community intervention. Our learning community was comprised of one collegiate summer league head baseball coach and three coach educators (i.e. facilitators). Data were collected via eight weekly learning community meetings (i.e. recorded and transcribed), the coach's daily journal and post-learning community meeting journal, and the memory of his coaching experiences. The findings, which suggest a potential framework for sustaining an effective learning community, resulted in six themes (i.e. problem setting, problem sharing, questioning to prompt reflection, prescribed suggestions, collaborative solutions and psychological wellness) that describe the coach's experiences both internal and external to the learning community. The findings are discussed in relation to research on learning communities, experiential learning and reflection. Furthermore, we provide implications for future research by considering the learning community's influence on the head coach's reduction of stress and the utilisation of technology to sustain a stable learning community setting.